Impact of Intestinal Lavage on the Development of Pneumonia in Patients with Acute Poisonings by Psychopharmacological Agents - V. A. Matkevich; E. A. Luzhnikov; K. K, Ilyashenko; S. I. Petrov; V. P. Nikulina; N. V. Evdokimova (Общая реаниматология, 2011)
Objective: to evaluate the impact of intestinal lavage (IL) on the incidence of pneumonia in patients with poisonings by psychopharmacological agents (PPA). Subjects and methods. The incidence of pneumonia as a complication of acute oral poisonings by PPA was studied in 393 patients with moderate and severe poisonings. Of them, 112 patients underwent IL as a detoxification method; the other patients received standard blood detoxification methods in a package of remedial measures. The time course of changes in the blood levels of gram-negative intestinal bacterial lipopolysaccharide (LPS) and immune status were studied before and after IL. Results. Prior to treatment, 65% of the patients with PPA poisoning were found to have an 8—10-fold excess in the reference values for blood LPS. At the same time, there were suppressed immunogram readings. After IL, there was a 1.5-fold decrease in blood LPS levels, which remained during 3 days, and activation of immune processes. It was shown that the patients undergoing IL developed pneumonia as a complication of PPA poisoning 1.6 times less frequently and died of pneumonia 16 times less often. Conclusion. The better results of IL treatment are obviously associated with enteral detoxification, reduced enterogenic toxemia, and improved hemostatic parameters, which was accompanied by normalized neutrophil oxygen metabolism and lower exposure of lung tissue to reactive oxygen species. Key words: acute poisonings, endotoxins, enterohumoral barrier, pneumonia, intestinal lavage.